DECISION-MAKING ALGORITHM FOR SKIN TEAR TREATMENT: TRANSLATION AND CROSS-CULTURAL ADAPTATION. - de Melo dos Santos, Camyle; Baptista de Oliveira, Beatriz Guitton Renaud; LeBlanc, Kimberly; Alfradique de Souza, Priscilla (Enfermagem Atual in Derme)
Introduction: The Skin Tear Decision Algorithm, developed by the International Skin Tear Advisory Panel (ISTAP) in 2013, standardizes the prevention and treatment of skin tears through a systematic approach. Objective: To translate and cross-culturally adapt the Skin Tear Decision Algorithm into Brazilian Portuguese. Method: Methodological research conducted in five stages: (1) initial translation; (2) synthesis of translations; (3) back-translation; (4) expert committee, composed of 28 professionals; and (5) pre-test with 31 clinical nurses. The expert committee analysis included calculating the agreement rate and content validity index. In the pre-test, feasibility was assessed using the agreement rate. Results: The algorithm encompasses essential care in managing skin tears, including wound assessment, bleeding control, cleansing, approximation of wound edges, classification, and definition of therapeutic goals. The expert committee evaluation showed satisfactory results, with an agreement rate exceeding 80% and a content validity index above 0.80. In the pre-test, the translated version achieved a 100% agreement rate, a content validity index of 1.00, and a Kappa index of 0.846. Conclusion: The instrument SKIN TEAR: decision algorithm was considered feasible and feasible, aiming to significantly assist in the process of building a structured care program including the construction of prevention and treatment protocols for this type of injury contributing to the quality of health services.